Electromagnetically Transparent Graphene Respiratory Sensors for Multimodal Small Animal Imaging. Issue 21 (23rd September 2020) - Tweedie, Martin E. P.; Kersemans, Veerle; Gilchrist, Stuart; Smart, Sean; Warner, Jamie H.
Abstract: Magnetic resonance imaging (MRI) and computed tomography (CT) imaging with X‐rays are crucial diagnostic techniques in medicine, especially in oncology for evaluating the response to treatment. Body movement causes image blurring and synchronized gating to the respiratory and cardiac cycles is required. Degradation of MRI and CT imaging by the presence of metal in electronic respiratory sensors has limited their use, with a preference for pressure balloons for detecting respiration, but these are cumbersome and insensitive. Here, graphene's role is studied as an electromagnetically transparent electrode in a piezoelectric graphene respiratory sensor (GRS) device designed specifically for dual gated MRI and CT imaging of small animals. The GRS is integrated into a 3D‐printed cradle with all‐carbon‐based device life support (heating pad) and monitoring of small animals (electrocardiogram), enabling both heartbeat and respiration detection, significant improvements to throughput and reproducibility, and reduced animal suffering. This shows graphene's potential for a wide range of electromagnetic transparent electronics for medical imaging and diagnostics, beyond conventional metal electrodes. Abstract : Large area monolayer graphene is used as an electromagnetically transparent conductive electrode in a polymer based piezoelectric transducer with outstanding performance for sensing the breathing and heartbeats of small animals within custom designed all carbon‐based life support systems built for magnetic resonance imaging and computed tomography imaging. Clear high‐resolution gated images are obtained during use in oncology research.